Spontaneous coronary artery dissection: a report of three cases and review of the literature. Issue 818 (December 1993) - Kearney, P.; Singh, H.; Hutter, J.; Khan, S.; Lee, G.; Lucey, J.
Abstract : We describe the clinical course of three patients who developed spontaneous coronary artery dissection. All patients were young women, one 9 weeks pregnant. All presented with chest pain; one died suddenly proving refractory to resuscitation, another developed unstable angina culminating in myocardial infarction, cardiogenic shock and death, and the third patient underwent coronary artery bypass grafting following diagnosis of a spontaneous coronary dissection of the left anterior descending artery at angiography. Pathological findings in the two fatal cases are reported. This condition, although rare, is a prominent cause of ischaemic coronary events in young women, when it is frequently associated with pregnancy or the puerperium. Most patients die suddenly, but a clinical spectrum is seen including stable and unstable angina, myocardial infarction and cardiogenic shock. The left anterior descending artery is most frequently affected. The classical histological finding is that of a large haematoma occupying the outer third of the media resulting in complete compression of the true lumen. The cause of spontaneous dissection remains unclear but theories of aetiology include a medial eosinophilic angiitis, pregnancy-induced degeneration of collagen in conjunction with the stresses of parturition, and rupture of the vasal vasorum. The diagnosis must be considered when a patient presents with a suggestive clinical profile. Urgent angiography should be undertaken to establish the diagnosis and consideration given to the need for coronary artery bypass grafting, which has been successfully employed in a number of patients. The uneventful long-term survival of cases treated conservatively has been reported.